Irrigation Management Strategy for Rice–Fish Farming as a Conflict Resolution between Farmers and Pond Owners in Kelingi Tugumulyo - Gunawan, Hendra; Rejo, Amin; Adam, Muhammad; Alfitri, Alfitri (Jurnal Pemerintahan dan Politik Lokal, 2025)
Management of Water Resources in irrigation areas is a vital aspect in supporting food security and community welfare. The Kelingi Tugumulyo Irrigation Area, located in Musi Rawas Regency and Lubuk Linggau City, is one of the important irrigation areas in South Sumatra. This area serves not only as a rice production center, but also as a location for the development of heavy-water pond fish farming. However, differences in interests between rice farmers and fish farmers often trigger water use conflicts. This study aims to identify the dynamics of water use conflicts, assess the role of local institutions, and formulate sustainable policy solutions. The method used is a descriptive qualitative approach with the support of quantitative data from BPS, BBWs Sumatra VIII, and field surveys. The results showed that the conflict was triggered by imbalances in water distribution, weak regulation, low compliance with water utilization permits, and institutional helplessness of farmers (P3A). The impact of the conflict is a decrease in rice harvest area, land conversion to non-rice sector, as well as socio-economic inequality among water user groups. This study recommends strengthening regulation, revitalization of P3A/GP3A institutions, integration of cropping patterns and fish farming, as well as the application of water-efficient irrigation technology.